The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.immuni.2012.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Apoptosis by Disruption of the STAT3-IκB-ζ Signaling Pathway in Epithelial Cells Induces Sjögren’s Syndrome-like Autoimmune Disease

Abstract: Sjögren's syndrome (SS) is an autoimmune disease characterized by exocrinopathy that leads to dry eye and mouth. Although lymphocyte infiltration into exocrine glands and the generation of autoantibodies have been reported in SS, its pathogenic mechanism remains elusive. Here, we show that mice lacking the transcriptional regulator IκB-ζ developed SS-like inflammation characterized by lymphocyte-infiltrated dacryoadenitis and SS-associated autoantibodies. In particular, epithelial cells, but not hematopoietic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
138
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(150 citation statements)
references
References 61 publications
7
138
3
Order By: Relevance
“…Our findings that both JAK/STAT and NF-κB pathways are important for the synergism are consistent with a previous report on CXCL10 (3). Although STAT3 is known to play a very important role in inducing Nfkbiz expression in immune cells among the STAT family (9,11,12), the central STAT molecule acting downstream of IFN-γ signaling is STAT1 or STAT2 rather than STAT3 (1,15). The precise role of STATs in the regulation of Nfkbiz expression seems to be complicated and further analysis is needed.…”
Section: Effects Of Selective Inhibitors On Nfkbiz Expression In Kerasupporting
confidence: 93%
“…Our findings that both JAK/STAT and NF-κB pathways are important for the synergism are consistent with a previous report on CXCL10 (3). Although STAT3 is known to play a very important role in inducing Nfkbiz expression in immune cells among the STAT family (9,11,12), the central STAT molecule acting downstream of IFN-γ signaling is STAT1 or STAT2 rather than STAT3 (1,15). The precise role of STATs in the regulation of Nfkbiz expression seems to be complicated and further analysis is needed.…”
Section: Effects Of Selective Inhibitors On Nfkbiz Expression In Kerasupporting
confidence: 93%
“…by its requirement for Th17 differentiation and expression of particular pro-inflammatory cytokines. Nevertheless, Nfkbiz Ϫ/Ϫ mice show a pro-inflammatory phenotype and M1 hyperpolarization of macrophages (15,16,24,25), suggesting that so far unknown anti-inflammatory mediators might be controlled by IB. In this study, we found that induction of the potent anti-inflammatory cytokine IL-10 by LPS but also by TLR2 agonists (data not shown) was strictly dependent on IB and strongly reduced in Nfkbiz Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several other proinflammatory gene products, including IL-6, IL12p40, IL-17, IFN␥, and GM-CSF, have been found to be regulated by IB (16, 19 -23). Intriguingly, however, despite impaired expression of these pro-inflammatory cytokines, Nfkbiz Ϫ/Ϫ mice display a pro-inflammatory phenotype characterized by periocular inflammation, inflammatory skin alterations, and an M1 hyperpolarized macrophage state (15,16,24,25). In view of the phenotype of Nfkbiz Ϫ/Ϫ mice, we therefore investigated a potential role of IB for the regulation of IL-10 as an essential anti-inflammatory cytokine.…”
mentioning
confidence: 99%
“…Furthermore, enhanced apoptosis has been related to the impairment of secretory function and generation of autoantigens (17). More recently, it was shown that administration of caspase inhibitors in mouse models of SS ameliorated inflammation, indicating a critical role for caspase-mediated apoptosis (32). The decrease in TNF-␣-mediated caspase-3 activation observed here suggests that AT-RvD1 blocks molecules upstream of caspase-3 (e.g., caspase-8 or TNF receptor type 1; Fig.…”
Section: Discussionmentioning
confidence: 99%